Assessment of Students’ Application of Binary Concept Using Computer-Science-Unplugged-Method in A Selected Secondary School in Ilorin, Kwara State, Nigeria - Kehinde Muritala Nuhu; Nafisat A. Adedokun-Shittu; Caleb Asiyanbola; Adedeji Hammed Ajani (Universitas Pendidikan Indonesia (UPI), 2023)
Computer Science (CS) Unplugged is a method of teaching for introducing non-specialists to concepts of CS through hands-on activities that do not require the use of a computer. Often the deeper concepts of CS have been considered as being too difficult for secondary school students in Nigeria. CS Unplugged methods have been used successfully with students of a wide range of ages in foreign countries. In this regard, it is germane to investigate if students can apply the activities of CS Unplugged to a real-life situation in Nigeria using the binary concept. Thus, we need to investigate students’ application level of binary concepts using CS Unplugged in secondary schools. The study adopted a one-short case pre-experimental design with an intact class of 15 Senior Secondary School One (SS I) students. The result revealed that students were able to apply the binary concept in a real-life situation with no gender difference established. The findings thus implied that if CS concepts are taught using the CS-Unplugged approach, students would be able to apply computer science concepts to real-life situations thereby imbibing their problem-solving skills. It was thus recommended among others that secondary school teachers should make use of the CS Unplugged method since it exposes students to activity-based learning and it makes them relate the activities to a real-life situation.